A survey of end user and health care professionals experience of discomfort as related to intermittent catheterisation - Angie Rantell; Barbara Kearns; Hanny Cobussen-Boekhorst; Kay Willard; Rene Zonderland (Continence)
Background and Methods:: Clinical evidence around discomfort experienced at the various stages of the intermittent catheterisation (IC) journey is limited. This research aimed to gain insights into discomforts encountered at initiation of IC and when products were changed/swapped during their lifetime of use. To gather a range of viewpoints, digital questionnaires were distributed to End Users and to Health Care Professionals (HCP’s) to consider how discomfort has/may be experienced and managed. Results:: The surveys were completed by ninety nine End Users and 113 HCP’s. The results highlighted the variety of different ways in which discomfort may be described. For those End Users with urethral sensation, 89% stated the discomfort experienced acclimated i.e. they no longer felt the discomfort after a couple of days catheterising. Elements associated with improved experienced included End user education and how expectations were managed. Conclusions:: The findings highlight the need to ensure that all End Users receive adequate education and counselling to manage all aspects of IC not only when they start their journey of IC, but also on product switching and during their lifetime of use and that this should be tailored to their individual needs. By having a better understanding in relation to discomfort it may help HCP’s to understand challenges faced, prepare End Users and set their expectations, and aid the development of more evidence-based education and training for IC users.